Comparative performance and draughtability of buffaloes and cows during summer and winter - SINGH, S V; UPADHYAY, R C (The Indian Journal of Animal Sciences, 2013)
To determine suitability of the female buffaloes and cows for work, 10 crossbred cows and 10 female buffaloes, which included 5 dry non-pregnant (DNP) and 5 lactating non-pregnant (LNP), were used in pairs for ploughing during summer and winder. The ploughing was carried out in loam soil with a wooeden plough and traditional double neck yoke. The average width and depth of furrow cut by plough was 18 and 21 cm respectively. The speed of cows was more than buffaloes. The average working time was longer during winter than summer in both the species. The average horse power (hp) developed by cows was 0.54-+0.05 and 0.52-+0.12 and by buffaloes 0.47-+0.04 and0.47-+0.12 during summer and winter respectively. The study concluded that buffaloes and cows may be used for light to moderate work without any adverse effect on body functions.